LANGUAGE AND ACADEMIC IDENTITY: SOCIOLINGUISTIC ASPECTS OF ENGLISH AS A LINGUA FRANCA IN THE SCIENTIFIC COMMUNITY - Podhovnik, Edith (PEOPLE: International Journal of Social Sciences, 2015)
Language is closely connected to personal, social, and cultural identity. The article Language and Academic Identity: Sociolinguistic Aspects of English as a Lingua Franca in the Scientific Community describes the relationship between using English as a Lingua Franca (ELF) at universities and the image of the researcher in the scientific community. English has been widely recognised as the language of the international research community. Yet, while ELF has facilitated international co-operation and knowledge exchange, language choice has an effect on the researcher as an individual. Qualitative interviews with 40 lecturers and researchers at universities in Austria, Russia, Denmark, Ukraine, the Netherlands, Germany, Sweden, India, the UK, Slovenia, Mexico, France, Finland, and Saudi Arabia, conducted in May 2015, give an insight into the sociolinguistic aspects of using ELF. The survey shows that ELF is a language of communication as well as a language of identification in the scientific community. Currently, English has more status and prestige in the scientific community than other languages and attaches to the user the image of being a successful, international, bilingual or multilingual member of the scientific community.